Meta-Analysis of Cytokine Alterations in Schizophrenia: Clinical Status and Antipsychotic Effects - Miller, Brian J.; Buckley, Peter; Seabolt, Wesley; Mellor, Andrew; Kirkpatrick, Brian (Biological psychiatry (1969), 2011)
Schizophrenia is associated with immune system dysfunction, including aberrant cytokine levels. We performed a meta-analysis of these associations, considering effects of clinical status and antipsychotic treatment following an acute illness exacerbation. We identified articles by searching PubMed, PsychInfo, and Institute for Scientific Information and the reference lists of identified studies. Forty studies met the inclusion criteria. Effect sizes were similar for studies of acutely relapsed inpatients (AR) and first-episode psychosis (FEP). Interleukin (IL)-1β, IL-6, and transforming growth factor-β (TGF-β) appeared to be state markers, as they were increased in AR and FEP ( p < .001 for each) and normalized with antipsychotic treatment ( p < .001, p = .008, and p = .005, respectively). In contrast, IL-12, interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), and soluble IL-2 receptor (sIL-2R) appeared to be trait markers, as levels remained elevated in acute exacerbations and following antipsychotic treatment. There was no difference in IL-6 levels between stable medicated outpatients and control subjects ( p = .69). In the cerebrospinal fluid, IL-1β was significantly decreased in schizophrenia versus controls ( p = .01). Similar effect sizes in AR and FEP suggest that the association between cytokine abnormalities and acute exacerbations of schizophrenia is independent of antipsychotic medications. While some cytokines (IL-1β, IL-6, and TGF-β) may be state markers for acute exacerbations, others (IL-12, IFN-γ, TNF-α, and sIL-2R) may be trait markers. Although these results could provide the basis for future hypothesis testing, most studies did not control for potential confounding factors such as body mass index and smoking.